Discovery Learning : for Metacognition and Self Efficacy of Students of State Junior High School Ternate City - Ade Haerullah; Said Hasan; Tiara Pramesti C. Ibrahim (Jurnal Ilmiah Wahana Pendidikan, 2020)
The purpose of this study was to examine and determine the improvement of metacognitive ability and Self Efficacy of class VIII SMP Negeri 4 Ternate City in science subjects. This type of research uses an experimental method, namely research that is used to see a treatment and compare it. The results of this research show that metacognition in experimental class students has increased by an average of 71.75%, while metacognition in the control class is 55.65 then the Self Efficacy of experimental class students has increased by 63.12% while Self Efficacy in the control class is 60 ,28% This shows that the metacognition and Self Efficacy of the experimental class students is higher than the students' metacognition and Self Efficacy. Thus, it can be concluded that there is an effect of Discovery Learning on students' metacognitive abilities and Self Efficacy. In addition, the results of this study also show that there is a significant relationship between metacognitive ability and Self Efficacy if given the Discovery Learnin treatment.